2000
DOI: 10.1037/0022-0663.92.4.620
|View full text |Cite
|
Sign up to set email alerts
|

Is handwriting causally related to learning to write? Treatment of handwriting problems in beginning writers.

Abstract: The contribution of handwriting to learning to write was examined in an experimental training study involving beginning writers with and without an identified disability. First-grade children experiencing handwriting and writing difficulties participated in 27 fifteen-min sessions designed to improve the accuracy and fluency of their handwriting. In comparison to their peers in a contact control condition receiving instruction in phonological awareness, students in the handwriting condition made greater gains … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

17
264
0
18

Year Published

2008
2008
2015
2015

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 328 publications
(299 citation statements)
references
References 38 publications
17
264
0
18
Order By: Relevance
“…The velocity was much slower when writing a complex character than when writing a simple character (F [1,91] =129.81, p<0.001). The differences between the three groups were also significant in simple tasks (F [2,91] =3.62, p=0.031) and complex tasks (F [2,91] =3.12, p=0.049). Further- …”
Section: Motor Control Of Handwritingmentioning
confidence: 71%
See 4 more Smart Citations
“…The velocity was much slower when writing a complex character than when writing a simple character (F [1,91] =129.81, p<0.001). The differences between the three groups were also significant in simple tasks (F [2,91] =3.62, p=0.031) and complex tasks (F [2,91] =3.12, p=0.049). Further- …”
Section: Motor Control Of Handwritingmentioning
confidence: 71%
“…The mean (SD) time constants of the HWD-DCD, HWD-nDCD, and comparison groups were 14.64 (7.92), 7.64 (5.11), and 6.18 (5.23) practice times, respectively. The group factor was found to have a significant effect on the time constant required to achieve automation (F [2,91] =15.52, p<0.001). The post-hoc tests revealed that the difference between the HWD-DCD and HWD-nDCD groups and between the HWD-DCD and comparison groups reached statistical significance (both p<0.001).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations